Humoral immune response in dogs and cats vaccinated against rabies in southeastern Brazil - Albas,Avelino (2013)
Background Brazil holds annual nationwide public campaigns to vaccinate dogs and cats against rabies. The presence of rabies antibodies in these animals, which are among the main transmitters of rabies to humans, is a good indicator that they are immunized and protected. Methods In the present study we analyzed 834 serum samples from dogs and cats from the Southeast of Brazil (Presidente Prudente and Dracena cities), 12 months after the 2009 vaccination campaign. We used the technique known as rapid fluorescent focus inhibition test (RFFIT) and considered reactant those sera with values higher 0.5 IU/mL. Results and discussion Reactant sample results in Presidente Prudente were 153 (51.0%) for dogs and 59 (32.6%) for cats, and in Dracena 110 (52.1%) for dogs and 71 (50.0%) for cats. We discussed vaccine coverage of animals involved in this experiment, and observed low titers < 0.5 IU/mL, especially in cats from Presidente Prudente. Conclusion According to the results presented in our experiment, we suggest that titers below 0.5 IU/mL are worrisome and that, for multiple reasons, animals should be immunized against rabies in the period between public vaccination campaigns. Hence, the desired vaccine coverage was not accomplished, especially among cats from Presidente Prudente.